“Family intervention” – A key to unlock the psychiatric morbidities in transsexuals: A case series - Lakshmi Sanjay; Arun Selvaraj; Vinoth Krishna Dass; S Perarul (Annals of Indian Psychiatry, 2022)
Transsexuals, who form a part in LGBT community, face a great amount of distress due to social stigma and lack of family support. This case series emphasizes the effect of family stigma in three such transsexuals, who presented with psychiatric complaints. A definitive need for scientific research and its application exists to address this stigma and discrimination. ICD-10 criteria were used to diagnose the psychiatric morbidities. Standard scores (Hamilton Depression Rating Scale and Suicidal Affect Behavior Cognition Scale) were used to assess the severity. Familial, individual, and interpersonal level interventions were administered. Significant improvements were seen in two patients (received family therapy) and one patient who did not receive therapy continued to be distressed. Psychological interventions resulted in reducing the family stigma and psychiatric morbidities suffered by them. This is an effort to show the need for implementation of such standard protocols in health-care facilities to address the stigma faced by transsexuals.